2008
DOI: 10.1159/000121986
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Significant Recurrent Headache in Preclinical Familial Alzheimer’s Disease Mutation Carriers

Abstract: Background/Aims: A previous study found a high prevalence of headaches in persons with familial Alzheimer’s disease (FAD) due to a PSEN1 mutation. In our study we compared the prevalence of headaches between nondemented FAD mutation carriers (MCs) and non-mutation-carrying controls (NCs). Methods: A headache questionnaire that assessed the prevalence of significant headaches and diagnosis of migraine and aura by ICHD-2 criteria was administered to 27 individuals at risk for FAD. Frequency of significant headac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Though it is possible that the apparent increased frequency of headaches in persons with FAD is due to differential medication use (e.g., acetylcholinesterase inhibitors), most persons with NF-EAD were also on such medications. Furthermore, in a previous report [16] we observed an increased frequency of headaches in FAD mutation carriers who were in the preclinical stage of the disease and therefore none of them were on such medications. The current study corroborates the observation that FAD is of particularly young onset, often in the 40s, has an aggressive course, and is frequently associated with neurological abnormalities.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Though it is possible that the apparent increased frequency of headaches in persons with FAD is due to differential medication use (e.g., acetylcholinesterase inhibitors), most persons with NF-EAD were also on such medications. Furthermore, in a previous report [16] we observed an increased frequency of headaches in FAD mutation carriers who were in the preclinical stage of the disease and therefore none of them were on such medications. The current study corroborates the observation that FAD is of particularly young onset, often in the 40s, has an aggressive course, and is frequently associated with neurological abnormalities.…”
Section: Discussionmentioning
confidence: 83%
“…These guidelines may be insufficient as there are patients who lack a known or reliable family history for early onset dementia. Certain symptoms such as headaches and other neurological abnormalities are frequently associated with FAD, especially those cases due to PSEN1 mutations, and may reflect other neuropathology such as cerebrospinal fluid involvement [13, 14, 16, 17, 29, 30, 39]. Though it is possible that the apparent increased frequency of headaches in persons with FAD is due to differential medication use (e.g., acetylcholinesterase inhibitors), most persons with NF-EAD were also on such medications.…”
Section: Discussionmentioning
confidence: 99%
“…Though there are many clinical and pathological similarities between FAD and late-onset AD, FAD can have atypical clinical (e.g. seizures [22], headaches [23]), imaging [24], and pathological [25] features. In addition, age influences CSF biomarker levels and therefore the young age and the relative lack of comorbidity in young FAD mutation carriers makes comparison to late-onset AD more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these symptoms and problems are nonspecific; they are associated with many medical, neurological, psychiatric, and neurodegenerative conditions and disorders. Headaches, for example, are common in the general population (Lanteri-Minet et al, 2003;Rasmussen et al, 1991) researchers have recently reported that headaches are a risk factor for a later diagnosis of vascular dementia (Hagen et al, 2013) and headaches apparently are an associated feature of early-onset AD (Joshi et al, 2012;Ringman et al, 2008). It seems very unlikely, however, that headaches will emerge as a reliable and specific indicator of CTE given the high prevalence in the general population and in those with various health and mental health problems.…”
Section: Clinical Features Of Ctementioning
confidence: 99%